An abstract model for the process of deliberation within multiagent systems - Stankevicius, Alejandro G. (2001)
A multiagent system is no more than a collection of interacting autonomous agents. However, this interaction allows the system as a whole to perform tasks beyond the reach of its individual members. This clearly accounts for the boost in research geared towards pro tting from this interaction. Accordingly, this paper addresses the formal modeling of a common kind of interaction known as deliberation. Simply put, a group of agents deliberate whenever they need to come to a mutually accepted position on some matter. The proposed model stems from the newly developed trend of reinterpreting agent interactions as an exchange of arguments in the context of some theory of defeasible argumentation.